557 Supposed"Satellite 8Q" Chromosome Associated to a Growth Retardation and Neurology Development Delay. (October 2012) - Garcia, MT; Rodriguez, L; Benedit, M; Llana, I; Golmayo, L
Abstract : Polymorphisms are cytogenetic laboratory findings that in most cases are inherited without clinical repercussion, when they are found in a karyotipe usually none additional studies are carried out. One of the most common is the presence of a satellite (NOR: nucleolus organizer regions) on a non-acrocentic chromosome. These extra NOR regions generally result from a translocation between a NOR region of an acrocentric chromosome and a non-acrocentric chromosome and are easily confirmed by NOR-bands in laboratory. These translocations are usually terminal and have been described on multiple chromosomes, the most frequent involves de Y chromosome. We present a case with a satellite chromosome and clinical expression. A 24 months old girl was referred to our hospital with deeply postnatal growth retardation, dymosphic features, motor delay and seizures. Cytogenetic studies were requested and a satellite in a chromosome 8 (8qs) was founded. FISH showed on the abnormal chromosome 8 a hybridization signal much bigger than the one detected on the normal homologue, these suggest a 8q24 inverted duplication. Array-CGH analysis at 40 Kb resolution confirmed the duplicated region of 17.2 Mb in 8q24.1–q24.3, associated to a terminal 55 Kb deletion. Furthermore, a triplicated region of 76 Kb between the duplicated and deleted regions was detected. The diagnosis is a 46, XX invdupdel (8) de novo. With this case we want to show that properly cytogenetic studies are very important in order to define the "supposed satellite chromosome" and to find other chromosome abnormalities that could explain the clinical findings of some patients.